(untitled) (Baghdad Science Journal, 2020)
Mutans streptococci (MS) are a group of oral bacteria considered as the main cariogenic organisms. MS consists of several species of genus Streptococcus which are sharing similar phenotypes and genotypes. The aim of this study is to determine the genetic diversity of the core species of clinical strains of Streptococcus mutans, Streptococcus sobrinus and Streptococcus downei by using repitative extragenic palindromic (REP) primer. The DNA of the clinical strains of S. mutans (n=10), S. sobrinus (n=05) and S. downei (n=04) have been employed in the present study, which have been previously isolated from caries active subjects. The DNA of the clinical and reference strains was subjected to PCR amplification using REP primer. The phylogenetic dendrogram is constructed from the REP PCR banding profile by neighbour-joining method using PyElph 1.4 software. The size of the DNA amplicons generated by using REP primer were S. mutans (1500 bp to 250 bp), S. sobrinus (6000 bp to 250 bp) and S. downei (5000 bp to 400 bp). The results present common band at 480 bp in all the clinical strains of S. sobrinus. The current study is the first to demonstrate the genetic variety of S. sobrinus and S. downei by using REP primer. REP-PCR have been found to be a powerful method to study the molecular diversity of S. mutans, S. sobrinus and S. downei. Additionally, further studies are suggested to analyze the species specific bands and also to find the possibility to produce a new specific primer for S. sobrinus.